2012
DOI: 10.1186/1743-7075-9-3
|View full text |Cite
|
Sign up to set email alerts
|

A high calcium diet containing nonfat dry milk reduces weight gain and associated adipose tissue inflammation in diet-induced obese mice when compared to high calcium alone

Abstract: BackgroundHigh dietary calcium (Ca) is reported to have anti-obesity and anti-inflammatory properties. Evidence for these properties of dietary Ca in animal models of polygenic obesity have been confounded by the inclusion of dairy food components in experimental diets; thus, effect of Ca per se could not be deciphered. Furthermore, potential anti-inflammatory actions of Ca in vivo could not be dissociated from reduced adiposity.MethodsWe characterized adiposity along with metabolic and inflammatory phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 50 publications
5
50
1
1
Order By: Relevance
“…Cumulative energy intakes in mice fed the DIO (HF) diet were not different, and therefore, it cannot account for the differences in the body weight between mice fed the DIO diet alone and DIO diet with increased Ca, D, and Ca + D content. Several studies using growing mice have also found a decreased body weight gain in animals on a high-calcium diet [29,32,40]. In addition, it is well established that vitamin D (1,25(OH) 2 D 3 ) is essential for intestinal Ca 2+ absorption and bone growth and remodeling [6,15,16].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cumulative energy intakes in mice fed the DIO (HF) diet were not different, and therefore, it cannot account for the differences in the body weight between mice fed the DIO diet alone and DIO diet with increased Ca, D, and Ca + D content. Several studies using growing mice have also found a decreased body weight gain in animals on a high-calcium diet [29,32,40]. In addition, it is well established that vitamin D (1,25(OH) 2 D 3 ) is essential for intestinal Ca 2+ absorption and bone growth and remodeling [6,15,16].…”
Section: Discussionmentioning
confidence: 97%
“…Particularly, low calcium intake and a low vitamin D status are associated with an increased risk of secondary hyperparathyroidism, osteopenia, and bone fractures, whereas high calcium and high vitamin D intakes are considered as protective factors against osteoporosis [21][22][23][24][25]. Importantly, obesity is often associated with low concentration of circulating 25-hydroxyvitamin D (25[OH]D) and low calcium intake [25][26][27][28], and increased dietary calcium and vitamin D intakes can reduce body weight gain and weight and percentage of body fat in diet-induced obesity (DIO) [25,[29][30][31][32]. Therefore, it is plausible that obesity accompanied by a low 25(OH)D concentration and a low calcium intake can have detrimental effects on bone health.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the COL6␣3 cleavage product endotrophin has been shown to act as a macrophage chemoattractant (37). Previously, we have demonstrated that WAT macrophage infiltration is strongly correlated with body weight over a large range in nonobese and moderately obese mice (52,53), which is indicative of a normal physiological role for macrophages in the course of adaptational WAT expansion and remodeling. However, chronic and extreme obesity can lead to accumulation of classically activated, proinflammatory CD11c ϩ M1 macrophages (31,32).…”
Section: E242 Adipose Extracellular Matrix Phenotypes In Obesitymentioning
confidence: 98%
“…This suggests that macrophages have a functional role in "repair" of dysfunctional "injured" WAT and that chronic inflammation stemming from macrophage activation contributes to insulin resistance. However, we and others have shown that WAT macrophage infiltration markers are strongly correlated with body weight over a large range in nonobese and moderately obese DIO mice (52,53), supporting a normal physiological role for macrophages in the course of well-controlled WAT expansion and remodeling. DIO mouse WAT is enriched in macrophages with a combination of classic M1 and alternative M2 characteristics, and genes involved in remodeling and angiogenesis are upregulated (42).…”
mentioning
confidence: 99%
“…As previously reported, pre-fattened DIO mice fed NFDM had significantly improved glucose homeostasis and markedly lower liver triglycerides, despite minimal differences in body weight, adiposity, and adipose tissue inflammation between the three diet treatment groups [17,18]. In the current investigation, the impact of high-calcium and dairy on low abundance signaling lipids in pre-fattened mice was explored using a PLS-DA model similar to Cohort 1.…”
Section: Resultsmentioning
confidence: 90%